Uma experiência de produção de espaço coletivo na Ocupação Dandara: a comunidade real como horizonte teórico de uma assessoria - Helena Fatima Alves Martins Miranda Lana (2016)
This thesis presents a process of technical assistance in the production of a facility for collective use in Dandara land occupation. In its context there is a diversity of social actors: from activists in political organization to technical supporters in which architects play a main role. Although activists and supporters can contribute enormously to the occupation by giving it some level of legitimacy, their practices can reinforce relations of dependency through welfarism and constrain the autonomy of the occupants. This dependency is reflected by the stimulation of passivity and alienation of the occupants, which promoted the consolidation of a heteronomous power in the occupation. In order to disrupt these relations of dependency and heteronomy, the production of the facility had, as a theoretical benchmark the concept of real community as a place for the exercise of individual and collective autonomy opposed to the concept of traditional community as a place of guardianship and heteronomy. The process allowed observation of the limits to autonomy and consequently the limits to the real community and at the same time the means to stimulate autonomy benefits and thus glimpse the theoretical benchmark. It introduces a possible alternative to the conventional practice of architects in occupations. Instead of reinforcing relations of dependency, they can stimulate autonomy gains.